Preparation of silver colloids with improved uniformity and stable surface-enhanced Raman scattering - Meng, Wei (Nanoscale Res Lett, 2015)
Silver colloids of uniform shape and size are prepared by a two-step reduction. Small silver particles form initially by the rapid reduction of silver nitrate with sodium citrate at 100°C and then grow at 92°C. The reaction processes and resulting silver colloids are characterized by transmission electron microscopy, ultraviolet–visible absorption spectrophotometry, zeta-potential measurements, and Ag(+) concentration analysis. The surface-enhanced Raman scattering (SERS) activity of the silver colloids is then investigated, using crystal violet (CV) as a SERS probe. The silver colloids exhibit uniform shape and size and stable SERS activity. The average size of the silver particles is 47 nm (14% relative standard deviation), while the average sizes of the silver colloids prepared at 100°C and 92°C are 41 (30%) and 71 nm (33%), respectively.